2008
DOI: 10.1038/jhh.2008.64
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between dietary protein intake and blood pressure: results from the PREMIER study

Abstract: Observational and clinical studies suggest that high protein intake, particularly protein from plant sources, might reduce blood pressure (BP). To examine the association of dietary protein with BP, we analysed data from PREMIER, an 18-month clinical trial (n ¼ 810) that examined the effects of two multi-component lifestyle modifications on BP. We examined the association of protein intake with BP, and in particular the independent relationship of plant and animal protein with BP. Multivariable linear regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
4
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 37 publications
5
56
4
2
Order By: Relevance
“…Although the relationship between the dietary protein intake and blood pressure remains controversial (16,17), recent evidence from randomized controlled trials suggests that an increased intake of protein may lower blood pressure (18)(19)(20)(21)(22)(23)(24)(25). The slightly decreased levels of serum albumin observed in apparently healthy subjects in the present study may possibly result from an inadequate protein intake.…”
Section: Discussioncontrasting
confidence: 38%
“…Although the relationship between the dietary protein intake and blood pressure remains controversial (16,17), recent evidence from randomized controlled trials suggests that an increased intake of protein may lower blood pressure (18)(19)(20)(21)(22)(23)(24)(25). The slightly decreased levels of serum albumin observed in apparently healthy subjects in the present study may possibly result from an inadequate protein intake.…”
Section: Discussioncontrasting
confidence: 38%
“…Vegetable proteins showed an inverse association with BP (16)(17)(18), whereas animal protein predominantly did not show any relation with BP (16,(26)(27)(28)(29). Furthermore, by increasing the serine intake, the dietary fiber significantly decreased, whereas SFA significantly increased.…”
Section: Discussionmentioning
confidence: 77%
“…Serine is a non-essential amino acid that is needed to some of signaling pathways and biosynthetic functions including synthesis of glycine, cysteine, tryptophan, sphingolipids, posphatidylserine, DNA and RNA components, and remethylation of homocysteine; it further acts as one of the carbon unit donors in the folate cycle (14). Although serine is one of the prominent amino acids in proteins with vegetable source (15) and plant protein has inverse relation with BP (16)(17)(18), the findings of previous cross-sectional studies suggest no relation between dietary serine intake and BP (11,13). However, a recent investigation from the European Prospective Investigation into Cancer (EPIC) study demonstrated that higher serum concentration of serine is a strong predictor of hypertension development (19).…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al did not suggest that the source of protein was a factor in explaining the BP effect. However, the increased protein was from a plant source, and a recent study suggested that plant protein may contribute to BP lowering, whereas animal protein does not (5). Future studies should be conducted to apply this dietary strategy in a larger population to confirm its BP-lowering effect and to examine its effect in a different population whose dietary intake is similar to that of the typical American.…”
Section: Pao-hwa Linmentioning
confidence: 99%